1989
DOI: 10.1139/m89-110
|View full text |Cite|
|
Sign up to set email alerts
|

Survival of and plasmid stability in Pseudomonas and Klebsiella spp. introduced into agricultural drainage water

Abstract: Cell survival and plasmid stability in Pseudomonas fluorescens R2f and Pseudomonas putida CYM 318 containing respectively, plasmid RP4 and pRK2501, and Klebsiella aerogenes NCTC 418 harboring plasmid pBR322 were studied in sterile and nonsterile agricultural drainage water under both aerobic and anaerobic conditions and in the absence and presence of added nutrients. Both Pseudomonas strains survived well in sterile drainage water incubated aerobically, with or without added nutrients. However, Klebsiella aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…It has been shown that in E. coli (3), Aeromonas salmonicida (17), and Klebsiella spp. (28), the number of plasmids possessed by the cells also decreased dur- FIG. 11.…”
Section: Discussionmentioning
confidence: 95%
“…It has been shown that in E. coli (3), Aeromonas salmonicida (17), and Klebsiella spp. (28), the number of plasmids possessed by the cells also decreased dur- FIG. 11.…”
Section: Discussionmentioning
confidence: 95%
“…Many studies have investigated the survival of introduced microorganisms and the persistence of GEMMOs in natural or model ecosystems such as soil microcosms [1,2,[4][5][6][7][8]. Pseudomonads are seen as prime candidates to be used as vehicles of biocontrol functions to protect the rhizosphere against deleterious pathogenic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that inoculum level and/or nutrient amendment had a significant influence on the survival of CHA0‐Rif in lysimeter effluent water. Similarly, the addition of nutrients to microcosms prepared with agricultural drainage water had a positive effect on persistence of the rhizosphere isolate P. fluorescens R2f(RP4) inoculated at 6 log cells ml −1 [23]. Strain R2f(RP4) could still be detected in microcosms 1 year after inoculation [36].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, leaching of nutrients may also influence the ecology of inoculants transported to groundwater level. In microcosm experiments, the addition of diluted Luria Bertani medium to agricultural drainage water influenced maintenance of plasmid RP4 in P. fluorescens R2f and survival of the strain [23].…”
Section: Introductionmentioning
confidence: 99%